2018
DOI: 10.1038/s41590-018-0182-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivated PI3Kδ promotes self and commensal reactivity at the expense of optimal humoral immunity

Abstract: Gain-of-function mutations in the gene encoding the phosphatidylinositol-3-OH kinase catalytic subunit p110δ (PI3Kδ) result in a human primary immunodeficiency characterized by lymphoproliferation, respiratory infections and inefficient responses to vaccines. However, what promotes these immunological disturbances at the cellular and molecular level remains unknown. We generated a mouse model that recapitulated major features of this disease and used this model and patient samples to probe how hyperactive PI3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
195
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(229 citation statements)
references
References 57 publications
25
195
1
Order By: Relevance
“…3, B -D). This is consistent with previous observations of increased pro-and pre-B cells in the endogenous repertoire of Pik3cd GOF mice, as well as of pre-B and immature B cells in the BM of patients with PIK3CD GOF mutations (Avery et al, 2018;Preite et al, 2018;Stark et al, 2018;Wray-Dutra et al, 2018). As with WT cells, we observed dramatically reduced proportions of mature self-reactive Pik3cd GOF SW HEL B cells ( Fig.…”
Section: Development Of Self-reactive Pik3cd Gof B Cells In the Bmsupporting
confidence: 93%
See 2 more Smart Citations
“…3, B -D). This is consistent with previous observations of increased pro-and pre-B cells in the endogenous repertoire of Pik3cd GOF mice, as well as of pre-B and immature B cells in the BM of patients with PIK3CD GOF mutations (Avery et al, 2018;Preite et al, 2018;Stark et al, 2018;Wray-Dutra et al, 2018). As with WT cells, we observed dramatically reduced proportions of mature self-reactive Pik3cd GOF SW HEL B cells ( Fig.…”
Section: Development Of Self-reactive Pik3cd Gof B Cells In the Bmsupporting
confidence: 93%
“…6 C and Fig. S5), consistent with the decreased ability of Pik3cd GOF B cells to undergo class switch recombination (Avery et al, 2018;Preite et al, 2018;Wray-Dutra et al, 2018) and the paucity of IgG autoreactive antibodies in PIK3CD GOF patients (Fig. S1).…”
Section: Self-reactive Pik3cd Gof B Cells Form Spontaneous Plasmablassupporting
confidence: 74%
See 1 more Smart Citation
“…Consistently, mice lacking p110δ (a subunit of PI3K highly expressed in lymphoid cells) in a T cell‐specific manner could not generate Tfh cells . Conversely, enhanced levels of PI3K signaling in T cells caused by PTEN deficiency in mice or activation mutations in the p110δ catalytic subunit of PI3K in humans and mice showed elevated Tfh responses. Using in vitro‐activated CD4 T cells, we and others have shown that acute co‐stimulation of ICOS‐enhanced IL‐21 mRNA expression.…”
Section: Icos Signaling In Tfh Cellsmentioning
confidence: 86%
“…Proper localization of Tfh cells in the light zone (LZ), a substructure of the GC, appears to be critical for their correct function. 36,37 In addition to expressing high levels of CXCR5 and low levels of CCR7 and PSGL1, this is achieved by downregulating S1PR1 and EBI2. 5…”
Section: T-bcellinteractionsingerminalcentersmentioning
confidence: 99%